2006
DOI: 10.1080/01926230601047832
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiles in Liver from Mice Treated with Hepatotumorigenic and Nonhepatotumorigenic Triazole Conazole Fungicides: Propiconazole, Triadimefon, and Myclobutanil

Abstract: Conazoles are environmental and pharmaceutical fungicides. The present study relates the toxicological effects of conazoles to alterations of gene and pathway transcription and identifies potential modes of tumorigenic action. In a companion study employing conventional toxicological bioassays (Allen et al., 2006), male CD-1 mice were fed triadimefon, propiconazole, or myclobutanil in a continuous oral-dose regimen for 4, 30, or 90 days. These conazoles were found to induce hepatomegaly, to induce high levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 91 publications
3
66
1
Order By: Relevance
“…To meet these demands, here, a 28-day feeding study in the rat was conducted with three substances (cyproconazole, epoxiconazole and prochloraz) in a broad dose range conceiving a typical toxicological threshold level (based on a nOAeL derived from a regulatory guideline study divided by a safety factor of 100) up to a clear effect dose (nOAeLx10). The study protocol was based on a regulatory guideline (OecD Tg407), but additional molecular methods were performed, including toxicity pathway-focused low-density gene expression arrays with subsets of marker genes previously identified as triazole related (goetz and Dix 2009b;Tully et al 2006;Ward et al 2006). here, we report the results of this study.…”
Section: Introductionmentioning
confidence: 97%
“…To meet these demands, here, a 28-day feeding study in the rat was conducted with three substances (cyproconazole, epoxiconazole and prochloraz) in a broad dose range conceiving a typical toxicological threshold level (based on a nOAeL derived from a regulatory guideline study divided by a safety factor of 100) up to a clear effect dose (nOAeLx10). The study protocol was based on a regulatory guideline (OecD Tg407), but additional molecular methods were performed, including toxicity pathway-focused low-density gene expression arrays with subsets of marker genes previously identified as triazole related (goetz and Dix 2009b;Tully et al 2006;Ward et al 2006). here, we report the results of this study.…”
Section: Introductionmentioning
confidence: 97%
“…This work is part of a larger toxicogenomic study (Ward et al, 2006) aimed at determining the mode(s) of action for these selected hepatotumorigenic conazoles.…”
Section: Introductionmentioning
confidence: 99%
“…Conazoles exert their effect by inhibition of the fungal lanosterol-14R-demethylase CYP51, thereby blocking the biosynthesis of ergosterol, an essential element of fungal cell membranes. Several toxic effects of conazoles have been observed in mammalian systems, including activation of nuclear receptors (CAR, PXR and PPAR) and induction of CYPs [168]. Kenneke et al reported a dose-dependent inhibition of the conversion of triadimefon to triadimefol by glycyrrhetinic acid with an IC 50 of 31 nM [167].…”
Section: Non-steroidal Carbonyl Compounds As Substrates Of 11␤-hsd1mentioning
confidence: 98%